Valence-engineered MoNi4/MoOx@NF as a Bi-functional electrocatalyst compelling for urea-assisted water splitting reaction. (1st August 2020) - Meng, Lingshen; Li, Liping; Wang, Jianghao; Fu, Sixian; Zhang, Yuelan; Li, Jing; Xue, Chenglin; Wei, Yanhua; Li, Guangshe
Abstract: Valence engineering was initially studied to achieve advanced bi-functional electrocatalysts for optimum performance. For this purpose, TMoO4 nanorods (T = Ni, Mn, Cu, and Zn) were grown on nickel foam, which upon reduction treatments, transformed into a composite system MoNi4 /MoOx @NF with alloy nanoparticles MoNi4 anchored on MoOx at 3D nickel foam. This composite system was demonstrated to show distinct mixed valence features of Mo 0 /Mo 2+ /Mo 4+ /Mo 5+ /Mo 6+ . When taken as a bifunctional electrocatalyst, this composite gives a lower surface charge transfer resistance, a lower Tafel slope, and an excellent electro-catalytic performance with 0.01 V for hydrogen evolution reaction and 1.29 V for urea oxidation reaction vs. reversible hydrogen electrode (RHE) at 10 mA cm −2 . Valence engineering of Mo species achieved by tuning the reduction conditions makes the electron density of Mo improved and Tafel-Heyrovsky step significantly increased. Under a reduction atmosphere for 2 h, the composite shows an optimum performance as represented by a much better electron conduction efficiency, a faster rate of Heyrovsky step, and a long-term stability at 10 mA cm −2 .